Diagnostic Value of Galectin-3, HBME-1, Cytokeratin 19, High Molecular Weight Cytokeratin, Cyclin D1 and p27(kip1) in the Differential Diagnosis of Thyroid Nodules - Park, Young Joo (The Korean Academy of Medical Sciences, 2007)
The distinction between benign and malignant thyroid tumors is critical for the management of patients with thyroid nodules. We applied immunohistochemical staining for galectin-3, HBME-1, cytokeratin 19 (CK19), high molecular weight cytokeratin (HMWCK), cyclin D1 and p27(kip1) in 295 thyroid lesions to determine their diagnostic accuracy. The expression of all markers was significantly associated with differentiated thyroid carcinoma (DTC).The sensitivity for the diagnosis of DTC was 94.7% with galectin-3, 91.3% with HBME-1, and 90.3% with CK19. The specificities of these markers were 95.5%, 69.7%, and 83.1%, respectively. Combining these markers, co-expression of galectin-3 and CK19 or galectin-3 and HBME-1 was seen in 93.2% of carcinomas but in none of the benign nodules. Comparing follicular variant of papillary carcinoma (FVPC) with follicular carcinoma (FC), the expression of galectin-3, CK19, and HMWCK was significantly higher in FVPC. When comparing FC with FA, the expression of galectin-3 and HBME-1 was significantly higher in FC. These results suggest that 1) galectin-3 is a useful marker in the distinction between benign and malignant thyroid tumors, 2) the combined use of HBME-1 and CK19 can increase the diagnostic accuracy, and 3) the use of CK19 and HMWCK can aid in the differential diagnosis between PC and FC.